Dance of the Nomad A Study of the Selected Notebooks of A.D.Hope - McCulloch, Ann (ANU Press, 2010)
The notebooks of A. D. Hope are a portrait of the contradictory essence of the poet's intellect and character. Shot through with threads of self-awareness and revelation, Hope imbued his notebooks with irony and humour, forming them as a celebration of the joy and terror of human existence. Stripped of intimate revelation, the entries give witness to Hope's view that art is a superior force in the creation of new being and values, and a guide for the conduct of our lives. Seeking to find pathways through the maze of an intellectual life, this is a profound and timely contribution to Australia's literary scholarship. Ann McCulloch's analysis of this thematic selection of Hope's notebooks reveals him to be relentless in his experimentation with ideas. Revealing the originality of his thinking and the astonishing range of his reading and interests, this edition is a testament to the intellect of one of Australia's towering literary figures.